2018
DOI: 10.1007/s00005-018-0506-x
|View full text |Cite
|
Sign up to set email alerts
|

Humanized Mice as Unique Tools for Human-Specific Studies

Abstract: With an increasing human population, medical research is pushed to progress into an era of precision therapy. Humanized mice are at the very heart of this new forefront where it is acutely required to decipher human-specific disease pathogenesis and test an array of novel therapeutics. In this review, “humanized” mice are defined as immunodeficient mouse engrafted with functional human biological systems. Over the past decade, researchers have been conscientiously making improvements on the development of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 192 publications
(313 reference statements)
1
72
0
Order By: Relevance
“…However, the utility of a given model for studying RIHD is dependent on the method and type of immune engraftment. For example, CB-17-scid, NOD-scid, and NOG mice are highly suitable for oncological studies but have a low tolerance to radiation [190]. In studying normal tissue radiation toxicities in these mouse models, radiation doses may have to be reduced to obtain the same normal tissue pathologies as in common wild-type mice.…”
Section: Radiation Therapy and The Immune Responsementioning
confidence: 99%
“…However, the utility of a given model for studying RIHD is dependent on the method and type of immune engraftment. For example, CB-17-scid, NOD-scid, and NOG mice are highly suitable for oncological studies but have a low tolerance to radiation [190]. In studying normal tissue radiation toxicities in these mouse models, radiation doses may have to be reduced to obtain the same normal tissue pathologies as in common wild-type mice.…”
Section: Radiation Therapy and The Immune Responsementioning
confidence: 99%
“…Therefore, in our model, we performed a hydrodynamic gene delivery of human cytokines into humice, and found that we could markedly enhance the reconstitution and function of human immune cells subsets, without any undesirable side effects . Two previously reported transgenic humanized MC expressing mouse strains have both been used to investigate human MC responses to IgE stimulation . In this regard, the findings of Ito et al .…”
Section: Discussionmentioning
confidence: 87%
“…One approach to studying this involves the use of humanized mouse models . Humanized mice (HuMice) are immunodeficient mice that lack endogenous murine immune cells but are engrafted with human stem cells to generate a functional human immune system . Over the last several decades, more advanced HuMice have been introduced using the most immunodeficient mouse strain NOD scid IL2Rγc −/− (“NSG”) to allow for optimal engraftment of human cells.…”
Section: Introductionmentioning
confidence: 99%